2015
DOI: 10.1107/s2053229615015867
|View full text |Cite
|
Sign up to set email alerts
|

The hydrochloride and hydrobromide salt forms of (S)-amphetamine

Abstract: This version is available at https://strathprints.strath.ac.uk/54364/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Rhizoma Coptidis was commonly used in medicinal and food industries (Han et al 2019 ), especially in traditional oriental medicine for the treatment of gastroenteritis; therefore, the main function compounds from Rhizoma Coptidis , including coptisine, berberine, palmatine, epiberberine, and jateorhizine, were regarded as promising inhibitor candidates of rumen microbial urease. In addition, salt selection is a wide technique used in the biological and pharmaceutical industries to enhance physicochemical properties of drug molecules, such as bioavailability, stability, and solubility (Dennany et al 2015 ). It has been reported that half of all drug compounds are in medicinal therapy in the form of salt (Bharate 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rhizoma Coptidis was commonly used in medicinal and food industries (Han et al 2019 ), especially in traditional oriental medicine for the treatment of gastroenteritis; therefore, the main function compounds from Rhizoma Coptidis , including coptisine, berberine, palmatine, epiberberine, and jateorhizine, were regarded as promising inhibitor candidates of rumen microbial urease. In addition, salt selection is a wide technique used in the biological and pharmaceutical industries to enhance physicochemical properties of drug molecules, such as bioavailability, stability, and solubility (Dennany et al 2015 ). It has been reported that half of all drug compounds are in medicinal therapy in the form of salt (Bharate 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phenylethylamine (PEA) compounds (Scheme 1) have long been known to have a large variety of pharmaceutical and biological roles (e.g. Brown et al, 1979;Drew et al, 1978;Broadley, 2010;Dennany et al, 2015). Due to their favourable handling characteristics, several have been used in studies where relatively large numbers of salt forms of a given API have been crystallographically characterized and the structures then used to systematically investigate material properties.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the residual aconitine and yellow plant pigment may be efficiently removed from the preparative process of aconine. Specifically, salt forming is a traditional and widely used strategy (He et al, 2018) in the pharmaceutical industry and has proved to be a viable means to change the physicochemical properties of potential APIs (Dennany et al, 2015) without disturbing the inherent bioactivities (Rajput, 2014). Moreover, 50% of drug molecules are prepared as salts to be used in medicinal therapy (Kumar et al, 2008;Thackaberry, 2012).…”
Section: Introductionmentioning
confidence: 99%